Path Analysis on the Effect of Biopsychosocial and Economic Factors during Gestational Period on the Risk of Stunting and Development in Children under Five, in Nganjuk, East Java - Erike Yunicha Viridula; Bhisma Murti; Nunuk Suryani (Journal of Health Promotion and Behavior, 2016)
Background: There is growing evidence of the connections between slow growth in height early in life and impaired health and educational and economic performance later in life. Basic Health Research (Riset Kesehatan Dasar, Riskesdas) conducted by The Minister of Health in 2010, showed that prevalence of stunting in Indonesia was 35.6% of children aged under five years old. This study aimed to examine  path analysis on the effect of biopsychosocial and economic factors during gestational period on the risk of stunting and development in children under five, in Nganjuk, East Java.Subjects and Method: This was an analytic observational study with case control design.  This study was conducted at Bagor Community Health Center, Nganjuk, East Java.  A total sample of 150 children under five, consisting of 50 stunted children and 100 normal children, was selected for this study by  fixed exposure sampling. The dependent variables were stunting and development. The independent variables were  middle upper arm circumference (MUAC) and family support at pregnancy, low birthweight, maternal height, maternal schooling, and family income. The stunting was measured by anthropometry (weight for height). The child development was measured by Kuesioner Pra-Skrining Perkembangan (KPSP). Other variables were measured by a set of questionnaire. The data were analyzed by path analysis.Results: Low birth weight had direct negative effect on stunting (b=0.99; p=0.897). Maternal height (b=-2.58; p= 0.029), maternal education (b=-1.55; p=0.002), and family income (b=-1.30; p=0.002) had direct negative effects on stunting. Low birth weight (b=-0.27; p=0.253) and family income (b=-0.007; p=0.976) have negative but statistically non-significant effect on development. Maternal education had positive but statistically non-significant effect on development (b=2.16; p=0.883). MUAC (b=-4.60; p<0.001) had negative and statically significant effect on low birth weight. Family support  had positive but statistically non-significant on low birth weight (b=0.52; p=0.492). Maternal height had positive and statistically significant effect on MUAC (b=3.16; p<0.001). Family income had positive but statistically non-significant effect on MUAC (b=0.83; p=0.253).Conclusion: MUAC and maternal education have indirect, negative and statistically significant effect on stunting Maternal height, maternal education, and family income, have direct, negative, and statistically significant effect on stunting.Keywords: stunting, biopsychosocial, economic, gestational periodCorrespondence : Erike Yunicha Viridula. Masters Program in Public Health, Sebelas Maret University. Email: yunichasabdana@gmail.com.Journal of Health Promotion and Behavior (2016),  1(3): 180-189https://doi.org/10.26911/thejhpb.2016.01.03.05